Drug abuse prevention model using ADDIE and CBT for primary school students - Nunuk Suryani, Achmad Basari Eko W, Mulyoto, Sri Anitah W, (Opción, 2019)
This research aims to create and describe a model using ADDIE Approach and CBT equipped with educative games in preventing drug abuse. The study used qualitative research and ADDIE model for instructional design involved 32 subjects including 5 principles, 5 teachers, and 22 students. The final result of this research shows that the students stated agree (80%), stated good (70%), stated attractive (85%), and stated helpful (100%) in preventing drug abuse. In conclusion, the developed application can be considered as meeting criteria for interactive application, based on the users’ perspective.